2014
DOI: 10.4269/ajtmh.14-0142
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrients and Dengue

Abstract: Abstract. Dengue virus infection is the most widespread mosquito-borne viral infection in humans and has emerged as a serious global health challenge. In the absence of effective treatment and vaccine, host factors including nutritional status, which may alter disease progression, need investigation. The interplay between nutrition and other infections is well-established, and modulation of nutritional status often presents a simple low-cost method of interrupting transmission, reducing susceptibility, and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 65 publications
1
29
0
1
Order By: Relevance
“…Vitamin E has well known antioxidant properties, through its ability to donate a hydrogen group from its free hydroxyl group to the free radical, with the generation of a stable free radical form of vitamin E. However, a number of non-antioxidant activities of vitamin E have been demonstrated [ 21 ]. α-Tocopherol has been reported to have some effects in dengue patients [ 22 ] and has proposed benefits for influenza virus A infection [ 23 ], as well as possible activity against hepatitis B [ 24 ] and C [ 25 ]. In this study, α-tocopherol showed proviral effects, particularly in HEK293T/17 cells (Fig.…”
Section: Main Textmentioning
confidence: 99%
“…Vitamin E has well known antioxidant properties, through its ability to donate a hydrogen group from its free hydroxyl group to the free radical, with the generation of a stable free radical form of vitamin E. However, a number of non-antioxidant activities of vitamin E have been demonstrated [ 21 ]. α-Tocopherol has been reported to have some effects in dengue patients [ 22 ] and has proposed benefits for influenza virus A infection [ 23 ], as well as possible activity against hepatitis B [ 24 ] and C [ 25 ]. In this study, α-tocopherol showed proviral effects, particularly in HEK293T/17 cells (Fig.…”
Section: Main Textmentioning
confidence: 99%
“…Emerging evidence supports a role of micronutrients in neglected tropical diseases [ 20 ]. In a 2012 report on neglected zoonoses, WHO cited nutritional status as an underappreciated, underlying cause of death in zoonotic infections [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the serum levels of Fe, Zn and Mg were found to be unaltered in NS1 positive cases with or without IgM positivity, in cases with IgM positivity and in OFI group compared to healthy blood donors from both local rural and urban population. There is paucity of data on systemic analysis of serum micronutrient levels in DF cases, especially in relation to clinical severity except few studies on ferritin and Zn [24][25][26].…”
Section: Discussionmentioning
confidence: 99%